Does the pain-protective GTP cyclohydrolase haplotype significantly alter the pattern or severity of pain in humans with chronic pancreatitis? - Anderson Michelle A; Dai Feng; Barmada M Michael; Lamb Janette; Lazarev Mark; Max Mitchell B; Whitcomb David C (SAGE Publishing, 2008)
Abstract Background Pain is often a dominant clinical feature of chronic pancreatitis but the frequency and severity is highly variable between subjects. We hypothesized that genetic polymorphisms contribute to variations in clinical pain patterns. Since genetic variations in the GTP cyclohydrolase (GCH1) gene have been reported to protect some patients from pain, we investigated the effect of the "pain protective haplotype" in well characterized patients with chronic pancreatitis (CP) or recurrent acute pancreatitis (RAP) from the North American Pancreatitis Study 2 (NAPS2). Results Subjects in the NAPS2 study were asked to rank their pain in one of 5 categories reflecting different levels of pain frequency and severity. All subjects were genotyped at rs8007267 and rs3783641 to determine the frequency of the GCH1 pain-protective haplotype. In Caucasian subjects the frequency of the pain-protective GCH1 haplotype was no different in the control group (n = 236), CP patients (n = 265), RAP patients (N = 131), or in CP patients subclassified by pain category compared to previously reported haplotype frequencies in the general Caucasian population. Conclusion The GCH1 pain-protective haplotype does not have a significant effect on pain patterns or severity in RAP or CP. These results are important for helping to define the regulators of visceral pain, and to distinguish different mechanisms of pain.